"Made in China" and Chinese Brand Management Across Cultures: A New Matrix Approach. Issue 1 (1st January 2021) - Polfuß, Jonas
Abstract: This study proposes a matrix that classifies and compares key forms of intercultural branding and brand communication among Chinese companies, focusing on Chinese brands that have developed in competition with foreign suppliers and have chosen different approaches to identity formation. Chinese branding since the 1980s and current brand communication on corporate websites are examined closely and the brand communication of established and emerging brands from China is identified. Moreover, representative marketing practices are provided to analyze firms' strategy development and predict future "Made in China" marketing efforts. The proposed matrix can be employed by future international and intercultural research.